Penyuluhan Literasi Media untuk Bijak di Media Sosial dan Pemanfaatan Media Digital - Dwiza Riana; Agus Subekti; Hilman F. Pardede; Zico Pratama Putra; Faruq Aziz (LPPM STKIP Kusuma Negara, 2022)
Understanding the power of media must be promoted at all levels. Efforts to develop media literacy, both in the form of thoughts and in conducting outreach activities, need to be carried out and supported by various stakeholders. Especially in the current era of digital media, people are used to and easily access social media. There is also growing concern about the negative impact of social media use on young people. Therefore, it is necessary to teach the younger generation media skills to use social media. This is the basis for making joint activities aimed at educating the younger generation to be wise in using social media and being able to use digital media well. This activity took place on April 3, 2022 with a total of 15 participants. Based on the results of the activities carried out, the application of positive communication resulted in positive changes in the insights, knowledge, skills, values, and attitudes of adolescents, and this activity has important benefits for community activities. to successfully achieve the goals and benefit the community, especially the partners of the SIGMA Foundation.